The Influence of Work-Life Balance and Physical Work Environment on the Performance of State Civil Apparatus Teachers (ASN) of NSF Cimahi Junior High School - Khaerani, Salma Fithri; Prabowo, Juddy (Syntax Corporation, 2025)
Based on the results of the teacher performance evaluation in 2022 and 2023, there has been a decline in teacher performance, suboptimal physical work environment conditions, and extra workloads that often extend beyond working hours. This study aims to analyze the influence of work-life balance and physical work environment on the performance of Civil Servant Teachers (ASN) at SMP NSF Cimahi. The research uses a quantitative approach with a census method, employing a questionnaire as a data collection tool. The research population includes 36 ASN teachers for the independent variable and 1 principal for the dependent variable. The results of the descriptive analysis show that the work-life balance of ASN teachers falls within the balanced criteria, with the sub-variable of balance being the highest value. The physical work environment falls into the good category, with the sub-variable of workplace safety being the highest value. The overall performance of teachers falls within the good criteria, with the highest sub-variable being social competence. The results of multiple linear regression show that work-life balance and physical work environment simultaneously influence the performance of ASN teachers at SMP NSF Cimahi with a high or strong level of impact. This research proves that a good work-life balance and a conducive physical work environment significantly contribute to the improvement of teacher performance at SMP NSF Cimahi. This research provides important contributions in supporting the development of policies to improve work-life balance and physical work environments to enhance teacher performance, which ultimately contributes to the quality of education.